DETERMINANT OF CHRONIC ENERGY MALNUTRITION OF PREGNANT WOMEN AT KARANG BANDAR LAMPUNG HEALTH CENTER - Mutiara Ayu Muthiatulsalimah; Sri Rahayu (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The most common nutritional problem experienced by pregnant women is Chronic Energy Deficiency (CED), which may be caused by nutritional intake consumed, socio-economic and history of disease / infection before becoming pregnant. But the cause of CED is not only a problem of lack of food but also due to the influence of lifestyle, workload and nutritional status of the mother during pregnancy. This study aims to determine the relationship between lifestyle during pregnancy, workload during pregnancy, nutritional status during pregnancy with Genesis CED in Pregnant Women. Methodology: Quantitative research method with cross sectional design. The population of this study were all pregnant women who checked their pregnancy at the Public Health Center Karang City Bandar Lampung. Sampling technique using total population sampling is as much as 40 people. Data was collected through primary (questionnaire) and secondary (KIA book) data collection. Data analysis was performed using chi-square test. Results: Results of this study showed that there was no significant relationship between lifestyle with the CED incidence in pregnant women. Meanwhile, the results showed that workload and nutrition were significantly associated with the CED incidence in pregnant women. Conclusion: This study recommends that there is a need for coordination between puskesmas and city health offices to provide supplementary food for pregnant woman and provide education to woman about the importance of nutrition during pregnancy before marriage, such as counseling in order to prevent CED occurrence during pregnancy. Keywords: Chronic Energy Deficiency, lifestyle, workload, pregnancy